2021
DOI: 10.3762/bjnano.12.50
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous and nonporous conjugated donor–acceptor polymer semiconductors for photocatalytic hydrogen production

Abstract: Conjugated polymers (CPs) as photocatalysts have evoked substantial interest. Their geometries and physical (e.g., chemical and thermal stability and solubility), optical (e.g., light absorption range), and electronic properties (e.g., charge carrier mobility, redox potential, and exciton binding energy) can be easily tuned via structural design. In addition, they are of light weight (i.e., mainly composed of C, N, O, and S). To improve the photocatalytic performance of CPs and better understand the catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…[9][10][11] In particular, significant advances in the preparation of conjugated microporous polymer (CMP) photocatalysts with high photocatalytic activity have been achieved. [12][13][14] Many studies revealed that designing a donor-acceptor (D-A) molecular structure is an efficient strategy to boost the photocatalytic activity of conjugated polymer photocatalysts, [15][16][17][18] since the intrinsic electron push-pull effect in a D-A conjugated polymer could promote the separation of light-induced hole/ electron. The nature of electron donor and acceptor units plays a key point in the charges transfer and separation, which affect significantly the photocatalytic activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] In particular, significant advances in the preparation of conjugated microporous polymer (CMP) photocatalysts with high photocatalytic activity have been achieved. [12][13][14] Many studies revealed that designing a donor-acceptor (D-A) molecular structure is an efficient strategy to boost the photocatalytic activity of conjugated polymer photocatalysts, [15][16][17][18] since the intrinsic electron push-pull effect in a D-A conjugated polymer could promote the separation of light-induced hole/ electron. The nature of electron donor and acceptor units plays a key point in the charges transfer and separation, which affect significantly the photocatalytic activity.…”
mentioning
confidence: 99%
“…In general, aromatic heterocyclic compounds with narrow band gap are commonly used as electron acceptors, and aromatic hydrocarbons with delocalized π-electron are employed as electron donors to build D-A type polymer photocatalysts. Based on the developed D-A polymer photo catalysts to date, [15,[19][20][21][22] dibenzo[b,d]thiophene-S,S-dioxide (BTDO) might be the most effective acceptor unit due to its strong electronwithdrawing capability and high hydrophilicity, [23][24][25] and pyrene with planar molecular structure and large delocalized π-electron system is the most effective electron donor to prepare high performance polymer photocatalysts. [26,27] Although there have been significant advances in the photo catalytic activity of polymer photocatalysts by structure optimization, [28,29] the limited scope of high efficient electron donors and acceptors hinders the further development of organic polymer photo catalysts.…”
mentioning
confidence: 99%
“…Donor-acceptor (D-A) conjugated polymers with alternating structures have emerged as promising photocatalysts for hydrogen generation [ 48 , 49 , 50 ], owing to the intramolecular pull-push effect of D-A structure that would promote electron (e − )/hole (h + ) separation in the presence of light irradiation [ 51 , 52 , 53 ]. To our knowledge, organic–inorganic heterojunctions composed of D-A type CPs and TiO 2 have rarely been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In this respect, D-A-type CPs are expected to serve as an ideal platform to explore highperformance photocatalysts. [15][16][17][18][19] The introduction of heteroaro-Scheme 1. Synthetic routes of HFBtBT X , FlBtBT X, SFBtBT X (X = 0, 0.01, 0.02, 0.05, 0.1, 0.2, 0.5), and BtBT (X = 1) via direct C-H arylation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] In this respect, D‐A‐type CPs are expected to serve as an ideal platform to explore high‐performance photocatalysts. [ 15–19 ] The introduction of heteroaromatic electron‐accepting and donating units has manifested as an effective strategy for designing CP‐based photocatalysts. [ 18–22 ] Wang et al.…”
Section: Introductionmentioning
confidence: 99%